EXPLORING SELAWAT AS A RELIGIOUS COPING STRATEGY FOR STRESS AMONG MUSLIM WOMEN EXPERIENCING DUAL-ROLE CONFLICT - Karyunah (Universitas Islam Negeri Jurai Siwo Lampung, 2026)
This study examines the role of selawat as a stress-coping mechanism among the Alhidayah female congregants in Kwasen, Pemalang, who experience dual-role conflict in balancing domestic and social responsibilities. Employing a descriptive qualitative design with a field research approach, data were collected through in-depth interviews, observation, and documentation, and analyzed using thematic analysis. The findings indicate that dual-role conflict arises from both internal and external factors and manifests in physical, emotional, and behavioral stress symptoms. The practice of selawat functions as a religious coping strategy by fostering emotional calmness, strengthening spiritual connection with God, and reinforcing social support through collective religious activities. These interconnected mechanisms enable participants to manage stress and adapt more positively to the demands of multiple roles. This study contributes to the growing literature on religious coping by demonstrating how selawat serves not only as a spiritual practice but also as a psychosocial resource for enhancing psychological well-being among women experiencing dual-role conflict. The findings further provide practical insights for integrating culturally and religiously grounded approaches into community-based mental health and counseling programs.